Pendampingan BUMDes dan Usaha Mikro Melalui Program Membangun Kemitraan Untuk Akses Modal - Muhammad Teguh; Harunnurrasyid Harunnurrasyid; Shelly Febriana Kartasari; Vinny Dwi Melliny; Gustriani Gustriani; Waldi Novi Yarsah (Kreativasi : Journal of Community Empowerment, 2024)
Villages, as the smallest sphere of society in the country, are often forgotten as an effort to realize it. To improve the village economy, BUMDes should be a body that has an important role. However, this is not reflected because Kembahang II Village itself only has one operating BUMDes, namely BUMDes Sumber Maju. Therefore, counseling and training related to BUMDes is needed for the village community. The community service team of the Faculty of Economics, Sriwijaya University, has conducted training on micro-enterprises through a program to build partnerships for access to capital and business financing in Ulak Kembahang II Village. The results obtained from the service training are the provision of educational material on how to manage micro businesses through the development of village business proposal profiles through the development of BUMDes so that later it can encourage the economic growth of Ulak Kembahang II Village to run well. The level of understanding of the participants who attended the training was evidenced by the level of thinking about the objectives and benefits of the training material that had been provided by 64.0% answering strongly agree and 36.0% only answering agree from the total number of participants present of 25 participants.